TWO SPECIES RESEARCH THE RELATIONSHIP BETWEEN DATA - Tajidinov Ilhomidin Nabijonovich; Nizomitdinova Guldona Farhodjon qizi (Web of Journals Publishing, 2024)
Understanding the relationships between data is crucial in various fields ranging from biology to artificial intelligence. In this study, we compare the approaches of two species, humans and artificial intelligence algorithms, in researching these relationships. Through a literature analysis, methods comparison, and results interpretation, we elucidate the strengths and limitations of each approach. Our findings shed light on the complementary nature of human and AI methodologies in data exploration.
Keywords: irony, humor, pragmatic principles, violation, commitment and critique, anaphoric reference, chardonnay.